Disseminated Intravascular Coagulation - Spero, Joel A; Lewis, Jessica H; Hasiba, Ute (Thrombosis and Haemostasis, 1980)
An analysis was made of 346 cases of disseminated intravascular coagulation (DIC) diagnosed by utilizing a combination of laboratory tests which reflect the pathophysiology of the syndrome. The goals of the study were three fold: 1) to compare our clinical disease categories with those of other investigators, 2) to re-evaluate the diagnostic tests and, 3) most importantly, to report the results of tests infrequently performed when evaluating DIC. The patients fell into the following groups: 1) infection – 26%, 2) malignancy – 24%, 3) surgery and trauma – 19%, 4) liver disease – 8%, 5) miscellaneous – 23%. Of the diagnostic tests, those for fibrin split products (FSP), fibrin monomer and antithrombin III were the most valuable. Of the clotting proteins, factors II, V, VII and X were the most frequently decreased. The factor VIII: C levels were in conflict with the prevailing dogma. Factor VIII :C levels were decreased in only 9% of patients studied and, in fact, were increased in the majority of cases. Factor VIIIR: Ag and F VIIIR: vW were elevated in 80% of the patients evaluated. An overall mortality of 68% further confirms the dismal prognosis previously associated with DIC.
Keywords: DIC; Fibrin monomers; Fibrin split products